RIFM fragrance ingredient safety assessment, 2-decanone, CAS Registry Number 693-54-9. (15th December 2020) - Api, A.M.; Belsito, D.; Biserta, S.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Cancellieri, M.A.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; et al.
Abstract: The existing information supports the use of this material as described in this safety assessment. 2-Decanone was evaluated for genotoxicity, repeated dose toxicity, reproductive toxicity, local respiratory toxicity, phototoxicity/photoallergenicity, skin sensitization, and environmental safety. Data from read-across analog 2-heptanone (CAS # 110-43-0) show that 2-decanone is not expected to be genotoxic. Data on read-across analog 2-heptanone (CAS # 110-43-0) provide a calculated margin of exposure (MOE) > 100 for the repeated dose toxicity and reproductive toxicity endpoints. The skin sensitization endpoint was completed using the dermal sensitization threshold (DST) for non-reactive materials (900 μg/cm 2 ); exposure is below the DST. The phototoxicity/photoallergenicity endpoints were evaluated based on ultraviolet (UV) spectra; 2-decanone is not expected to be phototoxic/photoallergenic. For the local respiratory endpoint, a calculated MOE >100 was provided by the read-across analog 4-methyl-2-pentanone (CAS # 108-10-1). The environmental endpoints were evaluated; for the hazard assessment based on the screening data, 2-decanone is not persistent, bioaccumulative, and toxic (PBT) as per the International Fragrance Association (IFRA) Environmental Standards. For the risk assessment, 2-decanone was not able to be risk screened as there were no reported volumes of use for either North America or Europe in the 2015 IFRA Survey. Highlights: 2-Decanone; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.